2021
DOI: 10.1177/10245294211031051
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of a New European Labour Policy regime: Continuity and change since the euro crisis

Abstract: The architecture of European labour policy has changed in the past years of the euro crisis and its management. While in the pre-crisis phase EU labour policy still had a mainly symbolic character, the EU crisis management gave it a much more binding character. The article analyses the continuities and shifts in European labour policy against the background of austerity and crisis policy arguing that a new labour policy complex was able to emerge at the European level. While institutional shifts were considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 84 publications
0
5
1
Order By: Relevance
“…Zeitlin and Vanhercke (2018) have found evidence for a socialization of the European Semester, lending credence to the Juncker Commission's claim of aspiring for ‘a more social Europe’. This is in contrast with the findings of other researchers (Copeland and Daly, 2018; Syrovatka, 2021a) who instead find that the policy recommendations of the Commission, as articulated in the Semester, veer in favor of market liberalization and a commodification of labour relations. More closely related to the topic investigated here, existing research on the Semester has focused on examining the determinants of CSRs in different policy areas.…”
Section: The European Semester and The Role Of The Commissioncontrasting
confidence: 97%
See 4 more Smart Citations
“…Zeitlin and Vanhercke (2018) have found evidence for a socialization of the European Semester, lending credence to the Juncker Commission's claim of aspiring for ‘a more social Europe’. This is in contrast with the findings of other researchers (Copeland and Daly, 2018; Syrovatka, 2021a) who instead find that the policy recommendations of the Commission, as articulated in the Semester, veer in favor of market liberalization and a commodification of labour relations. More closely related to the topic investigated here, existing research on the Semester has focused on examining the determinants of CSRs in different policy areas.…”
Section: The European Semester and The Role Of The Commissioncontrasting
confidence: 97%
“…First, because a greater monitoring of wage developments at the European level is not only recognized as important for the economic resilience of the Eurozone, but also because the Commission is playing an increasingly important role in the regulation of member states' labour markets. Recent initiatives such as the support and expansion of short-time work schemes or the proposal for the introduction of a directive on fair and adequate minimum wages across the EU are symptomatic of the Commission's increased willingness to intervene and promote greater coordination between member states' labour market policies (Syrovatka, 2021a). Second, while the mechanisms through which CSRs are implemented in national reforms programs constitute a promising avenue of further research (Guardiancich and Guidi, 2020;Mariotto, 2022), investigations into this area have shown that also non-binding CSRs on policy fields that are not within the remit of the EU's competences can have important consequences for member states' domestic policy agendas (Syrovatka, 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations